Efektivitas Simulasi Bantuan Hidup Dasar dengan Manekin dan AED bagi Karyawan PT. MAL - fernando, jansen; Dewi, Oktavia; Febiyan, Hafis Jauhar (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This study aimed to evaluate the effectiveness of Basic Life Support (BLS) training using a mannequin and AED simulation in enhancing the technical skills and confidence of employees at PT. Manggala Alam Lestari (PT. MAL) in handling sudden cardiac arrest in a remote work environment. Research Methodology: The program employed a Community-Based Research (CBR) approach, involving active participation from employees. The training design included simulation-based exercises using a mannequin and AEDs. Data were collected using pre- and post-test questionnaires to measure knowledge and confidence levels. Results: The training resulted in a significant increase in the participants' knowledge, as evidenced by the rise in average post-test scores from 40.75 to 92.75. The standard deviation decreased from 17.74 to 8.16, indicating greater consistency in understanding among participants post-training. Conclusions: BLS training effectively enhanced both technical skills and confidence among employees, aligning with previous research findings that highlight the benefits of simulation-based training in improving clinical skills and preparedness for emergency situations. Limitations: This study was conducted at a single site with a limited sample size, which may affect the generalizability of the findings. The long-term retention of skills was not assessed beyond the immediate post-training period. Contribution: This training model can be applied to similar workplaces, particularly in remote locations with limited access to medical facilities, to improve emergency preparedness and safety outcomes.